3D Research Challenges in Cultural Heritage IV: Risk Prevention and Monitoring Methods (Lecture Notes in Computer Science, 2025)
This open access book presents a collection of papers focusing on a range of digital technologies and their use in the protection and restoration of cultural heritage. Digital tools - from 3D scanning and photogrammetry to Heritage Building Information Modeling (HBIM), Digital Twins, and Extended Reality (XR) - are transforming the way we understand and care for tangible heritage. These technologies are applied to both record the physical form and material conditions of a site and to permit simulations of deterioration, design interventions, and careful reconstruction. A central theme of this volume is post-disaster restoration and how the scientific and technical aspects of restoration can be made accessible to a broader audience through innovative visualizations, interactive platforms and storytelling. Digital tools should not only serve experts but also allow the public to participate both on-site and remotely via the web. This book advocates a holistic approach to heritage management, combining cutting-edge technology with local knowledge, risk analysis with creative reuse, and positioning the act of restoration as a bridge connecting the past, present and future.